Selective distortion of body image by asynchronous visuotactile stimulation. (March 2018) - Perez-Marcos, Daniel; Martini, Matteo; Fuentes, Christina T.; Bellido Rivas, Anna I.; Haggard, Patrick; Sanchez-Vives, Maria V.
Highlights: Synchronous visuotactile stimulation of a real and a fake arm induces ownership of the fake one. Ownership of a fake arm does not alter the internal calibration of the body size. Asynchronous visuotactile stimulation leads to a perceived elongation of the lower arm. Thus, asynchronous multisensory stimulation, often used as baseline, is not a neutral condition. The correct internal calibration of the body size requires coherent multisensory inputs. Abstract: In the rubber hand illusion (RHI), a rubber hand is felt as being part of one's body. This illusion is evoked by providing synchronous visuotactile stimulation to the fake and real hands. Asynchronous visuotactile stimulation is known not to produce such an illusion of ownership, being commonly used as the control condition. Here we explored the impact of synchronous and asynchronous visuotactile stimulation on the body image. We combined the induction of the RHI with a quantitative test for the internal representation of body metrics (i.e., the positions of key fiducial points on the body relative to each other). We found a significant recalibration of the upper/lower arm lengths following asynchronous visuotactile stimulation. In particular, we observed a selective elongation of the lower arm, a distortion typical of deafferentation. Conversely, synchronous visuotactile stimulation did not alter the estimation of the arm segments' length. Our findings are consistent with a dynamic internal representation of body image that is continuously updated based on incoming multisensory information. Furthermore, the use of asynchronous multisensory stimulation as a neutral condition should be reconsidered since it introduces changes in the body image.